Analysis of solar irradiation available in the city of Encarnación (Journal on studies and research of academic knowledge, 2021)
An analysis of solar irradiation in the city of Encarnación was carried out, using trigonometric equations of the celestial sphere and the isotropic mathematical model of Liu and Jordan, centered on the monthly characteristic days. From reliable data on solar irradiation on the horizontal surface, monthly irradiation values were found for optimal angles of inclination of the collecting surface and also for an angle of 27° of annual inclination, a latitude value corresponding to Encarnación. With the obtained values, the curve of optimal inclination angles for a solar energy collecting surface, the daily global irradiation curve for said angles and the contribution of the irradiation components were determined. The systematization of the calculation allowed obtaining daily, monthly and annual irradiation information. The calculation program developed can also be applied to any latitude and angle of inclination of the energy collection surface. The values ​​and curves obtainable will be useful for sizing photovoltaic systems and solar thermal installations.
Keywords: Irradiation; Latitude; Optimal Angles; Irradiation curves